ESTIMATION OF COW-HEIFERS’ BODY STRUCTURE TYPE AT THE PRESENT STAGE OF SELECTION ON BREEDING FARMS OF DIFFERENT REGIONS OF UKRAINE - Pomitun, I.A.; Adminа N. G.; Osipenko, T.L.; Filipenko, I.D.; Admin, A. E. (Scientific Progress & Innovations, 2020)
The aim of the article is to estimate the type of first-calf cows’ body structure on breeding farms of differ-ent regions of Ukraine. The comparison of the body structure type of cow-heifers in different regions of Ukraine under the effect of management conditions has been conducted. The electronic database of the exte-rior characteristics of cows has been further developed, on the basis of which the corrective selection of breeding bulls to the maternal stock has been carried out to qualitatively improve most of the described characteristics of the external conformation in animals of dairy breeds. The method of linear classification of cow-heifer line type score in accordance with the requirements of the ICAR international scale, the data of breeding records, methods of variation statistics have been used in the process of study. As a result of the investigation a significant effect of the factor “farm” on some indicators of linear appraisal of the cow body structure score was found, it ranged from the minimum value for the udder depth (η2 = 8.7 %, p<0.05) to the maximum value for the animal height (η2 = 18.9 %, p<0.001). In accordance with the research results, the experimental animals, which were evaluated by the 9- and 100-point classification system, differed greatly in their parameters on all the farms. According to the results of four sets of external characteristics’ classifica-tion, the level of the external line type score expression was the best in cow-heifers at the state enterprise, research farm “Hontarivka”, which significantly exceeded that of cows on other farms (p<0.05). The condi-tions created by the first farm also affected milk productivity of cows. Daily milk yields of cow-heifers had positive correlations with the most of linear characteristics (p<0.01). The maximum value of milk yield cor-relation coefficient with the animal height (r = + 0.49) was revealed at the state enterprise, research farm “Hontarivka” and the minimum value of the correlation coefficient – with the posture and angle of pelvic limbs (r = + 0.11) was at the state enterprise, research farm “Hontarivka” and LLC Agro-firm “Slobozhan-ska”. Applying linear classification method in selection programs and including functional characteristics of external appearance along with main selection features into comprehensive estimation of cows will promote the acceleration of forming the desired exterior type and increasing the productivity of cows of the Ukraini-an Black and Red Spotted dairy breeds for the farms with intensive technology of milk production.